(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Ayurveda advocates fumigation as a method of sterilization and therapeutic tool for different infective diseases and mental disorders. However, it is not popular and proven scientifically hence there is great scope and prospects for research. For patient safety, fumigation is a regular protocol. Aim and Objectives: It is the need of the hour to search a safe, cheap, effective and easily available drugs for fumigation hence Maheshwar Dhoop-MD was chosen and compared its efficacy with control- Bacillocid. Material and Method: Study was performed in Shalakya (eye-ENT), Panchkarma procedure rooms and minor operation theatre by pre-post swab and Agar plate exposure on 2nd (MD) and 4th week (Bacillocid) monthly once each for total three months. The microbial load was estimated for different micro-organisms like bacteria, fungus etc and subjected to statistical analysis. Observation and Results: The study revealed that the effect of Dhoopana was significant in comparison with Bacillocidto control both during study period and follow up period up to 6 days against bacterias and fungus. Conclusion: It was found that MD is safe, cheap and equally efficient as Bacillocid (p<0.0001) with one-week residual effect.